Testing of postharvest IEC materials and training, Philippines - Bayogan E.V.; Bello D.B.; Urquiola M.A.J.; Secretaria L.B. (CGIAR, 2023)
The purpose of utilizing information, education, and communication (IEC) materials and training seminars in the field of postharvest studies on fruits and vegetables is to effectively convey and disseminate information regarding various postharvest techniques, as well as the appropriate handling and management practices for various commodities. Pre-testing of IEC materials is necessary to ascertain the level of comprehension among the intended recipients, ensuring that the given messages are effectively understood. Some of the communicative aspects evaluated during the pre-testing of IEC materials are language appropriateness, appropriate format for its target audience, text-heaviness, and graphic appeal (Pathfinder International, 2016).